THE EXPRESSIVE POWER OF THE HARMONIC PARAMETER AND OF THE FORM IN THE CYCLE OF LIEDS DIE SCHÖNE MÜLLERIN BY FRANZ SCHUBERT - Gabriela COCA (Studia Universitatis Babeş-Bolyai. Musica, 2013)
The purpose of this paper consists in the analyze of the unifying correspondences of structural, artistic, and musical content of the cycle of Lied Die Schöne Müllerin by Franz Schubert. The entire cycle of Lieds represents a unified whole, in which the Lieder which make up the cycle are combined in the form of chain although their shape, their tonal ethos, and their significance are different or even contrary. On the basis of this cycle of Lieds I tried to discover the effect of the internal energy forces, on a homogeneous structure, in the sensible world of Schubert’s musical creation.